2012
DOI: 10.1186/1741-7007-10-94
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin-based Self-organization of cell internalization during C. elegans gastrulation

Abstract: BackgroundGastrulation is a key transition in embryogenesis; it requires self-organized cellular coordination, which has to be both robust to allow efficient development and plastic to provide adaptability. Despite the conservation of gastrulation as a key event in Metazoan embryogenesis, the morphogenetic mechanisms of self-organization (how global order or coordination can arise from local interactions) are poorly understood.ResultsWe report a modular structure of cell internalization in Caenorhabditis elega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 57 publications
1
52
1
Order By: Relevance
“…Due to complex cell rearrangements during late stages of gastrulation, the global asymmetry is gradually transformed into superficial L/R symmetry with a symmetrically positioned midline (Figure 6c, left) [197]. A comprehensive analysis of these cell rearrangements uncovered a chiral collective migration phase which seems to be driven by cortical actomyosin dynamics (Figure 6c, right) [197]. This migration resembles the directional rotation in a plane.…”
Section: Elegansmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to complex cell rearrangements during late stages of gastrulation, the global asymmetry is gradually transformed into superficial L/R symmetry with a symmetrically positioned midline (Figure 6c, left) [197]. A comprehensive analysis of these cell rearrangements uncovered a chiral collective migration phase which seems to be driven by cortical actomyosin dynamics (Figure 6c, right) [197]. This migration resembles the directional rotation in a plane.…”
Section: Elegansmentioning
confidence: 99%
“…Importantly, this asymmetrically positioned midline is maintained during the time window of all major asymmetric inductions that differentially pattern left and right body halves [195,196]. Due to complex cell rearrangements during late stages of gastrulation, the global asymmetry is gradually transformed into superficial L/R symmetry with a symmetrically positioned midline (Figure 6c, left) [197]. A comprehensive analysis of these cell rearrangements uncovered a chiral collective migration phase which seems to be driven by cortical actomyosin dynamics (Figure 6c, right) [197].…”
Section: Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…However, laser cuts have shown that the low level of tension in neighboring cells does not decrease further as apical constriction begins (Roh-Johnson et al, 2012). Alternatively, cell division in neighboring cells might relieve tension on cells undergoing apical constriction, because dividing cells have been shown to spread along the surface of the embryo (Pohl et al, 2012;Chihara and Nance, 2012). However, divisions of neighboring cells are unlikely to contribute significantly to apical constriction of the endoderm precursor cells in C. elegans, because most of the apical cell shape changes occur when neighboring cells are not dividing (Roh-Johnson et al, 2012).…”
Section: Circumferential Actin-myosin Beltsmentioning
confidence: 99%
“…Integrated C. elegans strains expressing lifeact-fusion proteins expressed from pie-1 promoters have been described previously (Pohl et al, 2012;Singh and Pohl, 2014). Strain TH252 (Ppie-1::gpr-1::GFP) was kindly provided by H. Bringmann (Bringmann et al, 2007) …”
Section: Worm Strainsmentioning
confidence: 99%